Electrochemical Behaviour and Rapid Determination of L‐Dopa at Electrochemically Pretreated Screen Printed Carbon Electrode. Issue 10 (14th July 2015) - Rabinca, Andreea Alexandra; Buleandra, Mihaela; Balan, Adriana; Stamatin, Ioan; Ciucu, Anton Alexandru
Abstract A simple and rapid voltammetric method based on a disposable electrochemically pretreated screen‐printed carbon electrode is proposed for the determination of L‐dopa. Under optimum differential pulse voltammetry conditions a limit of detection of 3.6×10−7 M for L‐dopa was obtained. The method was successfully applied to the determination of L‐dopa in a commercial pharmaceutical formulation.